Retirement rules in Hungary: Gainers and losers - Tibor Czeglédi; Endre Szabó; Melinda Tir; András Simonovits (Hungarian Academy of Sciences, Institute of Economics, 2016)
Though the Hungarian pension system has been suffering from many erroneous rules, in the present paper we confine our attention to the rules of retirement in Hungary since 1990. In every pension system, there exist two rules which determine how the lifetime contribution (which is approximately proportional to the years of contributions) and the retirement age influence the benefit amount, respectively. As a benchmark, we use the system of nonfinancial defined contributions, simulating a mandatory life insurance and life annuity system. More generally, we speak of flexible retirement if adding a year to the contributions or the retirement age strongly increases the retirement benefit, opening the way to the flexible choice of the retirement age. Due to erroneous concepts, flexibility has only functioned in a very imperfect form in Hungary. Before 2011/2012, an exemption rule completed the two foregoing rules: if somebody had above the critical value (35-40) of years of contributions, he/she could use early retirement without significant benefit reduction. Since 2011/2012 two other rules have completed these rules: (a) as an exception, since 2011, rule Females 40 has rewarded any woman who had at least 40 years of rights with a full benefit; (b) as a rigid rule, since 2012, nobody could have retired before reaching the statutory retirement age except for category (a). Taking into account the dependence of monthly benefits on the lifetime average valorized wages, we assess the gainers and losers of the past and the present systems.
Keywords: H55; I14; J26; 330; normal retirement age; early retirement; years of contributions; rights; flexible retirement